Social Participation as an Autopoietic System? Analysis of Participatory Instances in Brazil - Pires, Isabela Batista; Pratschke , Anja (National Journal of City Management, 2025)
Objective – This article aims to critically analyze the Brazilian participatory system considering Theory of Autopoiesis. Methodology – Qualitative approach of a theoretical-analytical nature, based on a literature review and critical analysis of Brazilian participatory instances, articulating the contributions of the Theory of Autopoiesis (Maturana and Varela, 2003; Luhmann, 1989) with authors who discuss qualified social participation (Oliveira and Ckagnazaroff, 2023; Lüchmann, 2020) and resilience (Heinimann e Hatfield, 2017). Originality/Relevance – This article proposes an autopoietic analytical perspective on social participation, considering the participatory system as an autopoietic system capable of internal reorganization, self-production, and learning. Results – The analysis of the Brazilian participatory system through the lens of autopoiesis allows us to understand the capacity of each participatory instance to produce distributed cognition in a way that fosters urban resilience. Theoretical/Methodological Contributions – Proposal of an analysis based on five interdependent dimensions for an autopoietic participatory system: communicative diversity, social memory, organizational plasticity, territorial coupling, and institutional resonance. Social and Environmental Contributions – Understanding the participatory system as autopoietic provides insights for the development of resilient urban governance with institutional listening, valorization of territorial knowledge, and the promotion of autonomous citizens capable of facing contemporary social and environmental challenges.